The Implications of Cognitive Psychology for Computer-Assisted Instruction - Walsh, S. H. (Methods of Information in Medicine, 1989)
An information processing model is used to describe the learning process. The implications of some of these cognitive concepts are examined in the context of computer-assisted instruction.
Keywords: Computer-assisted Instruction; Psychology; Cognitive Psychology; Cognition